2016
DOI: 10.1128/microbiolspec.funk-0011-2016
|View full text |Cite
|
Sign up to set email alerts
|

Lichenized Fungi and the Evolution of Symbiotic Organization

Abstract: Lichen symbioses comprise a fascinating relationship between algae and fungi. The lichen symbiotic lifestyle evolved early in the evolution of ascomycetes and is also known from a few basidiomycetes. The ascomycete lineages have diversified in the lichenized stage to give rise to a tremendous variety of morphologies. Their thalli are often internally complex and stratified for optimized integration of algal and fungal metabolisms. Thalli are frequently colonized by specific nonlichenized fungi and occasionally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(15 citation statements)
references
References 110 publications
1
14
0
Order By: Relevance
“…In general, mycobionts which show a high specificity for algal partners tend to accept only single algal lineages (Piercey-Normore and DePriest, 2001;O'Brien et al, 2013;Leavitt et al, 2015;Magain et al, 2017;Kosecka et al, 2020;Mark et al, 2020;Pino-Bodas and Stenroos, 2020;Garrido-Benavent et al, 2021), while mycobionts which are generalist can associate with many different algal lineages (Wirtz et al, 2003;Muggia et al, 2013;Sadowska-Deś et al, 2014); this has also been reported for photobionts and their preference toward fungal partners (Peksa and Škaloud, 2011). Specific or generalist associations among lichen symbionts are not random, but rather are modulated by ecological, environmental and evolutionary factors (Beck et al, 2002;Miadlikowska et al, 2006;Leavitt et al, 2015;Grube and Wedin, 2016;Chagnon et al, 2019), which have significant impacts on the structure of lichen communities and species distribution (Muggia et al, 2014;Sork and Werth, 2014;Steinová et al, 2019). Many analyses have pointed out that climatic conditions are the most important factor shaping phycobiont distribution patterns (Kroken and Taylor, 2000;Helms et al, 2003;Fernández-Mendoza et al, 2011;Peksa and Škaloud, 2011;Řídká et al, 2014); however, the influence of factors such as phylogenetic and evolutionary specialization, reproductive strategy, the presence of compatible phycobionts as well as ecological factors should not be overlooked (Yahr et al, 2006;Muggia et al, 2013;Printzen et al, 2013;Singh et al, 2017;Ertz et al, 2018;Pardo-De la Hoz et al, 2018;…”
Section: Introductionmentioning
confidence: 90%
“…In general, mycobionts which show a high specificity for algal partners tend to accept only single algal lineages (Piercey-Normore and DePriest, 2001;O'Brien et al, 2013;Leavitt et al, 2015;Magain et al, 2017;Kosecka et al, 2020;Mark et al, 2020;Pino-Bodas and Stenroos, 2020;Garrido-Benavent et al, 2021), while mycobionts which are generalist can associate with many different algal lineages (Wirtz et al, 2003;Muggia et al, 2013;Sadowska-Deś et al, 2014); this has also been reported for photobionts and their preference toward fungal partners (Peksa and Škaloud, 2011). Specific or generalist associations among lichen symbionts are not random, but rather are modulated by ecological, environmental and evolutionary factors (Beck et al, 2002;Miadlikowska et al, 2006;Leavitt et al, 2015;Grube and Wedin, 2016;Chagnon et al, 2019), which have significant impacts on the structure of lichen communities and species distribution (Muggia et al, 2014;Sork and Werth, 2014;Steinová et al, 2019). Many analyses have pointed out that climatic conditions are the most important factor shaping phycobiont distribution patterns (Kroken and Taylor, 2000;Helms et al, 2003;Fernández-Mendoza et al, 2011;Peksa and Škaloud, 2011;Řídká et al, 2014); however, the influence of factors such as phylogenetic and evolutionary specialization, reproductive strategy, the presence of compatible phycobionts as well as ecological factors should not be overlooked (Yahr et al, 2006;Muggia et al, 2013;Printzen et al, 2013;Singh et al, 2017;Ertz et al, 2018;Pardo-De la Hoz et al, 2018;…”
Section: Introductionmentioning
confidence: 90%
“…They impact various community processes, also because of their rich and diverse secondary chemistry [3,4]. Recent studies have shown that lichens represent complex multi-species symbiotic assemblages, forming microhabitats and harbouring a high diversity of other eukaryotic and prokaryotic microorganisms [5,6,7]. High-throughput sequencing technologies have revealed the presence of multiple fungal and algal species, along with hyper-diverse bacterial communities, within individual lichen thalli [7,8,9,10,11,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Taxa with a lichen-forming mycobiont strategy characterized the majority of symbiotrophic. Fungi associated with lichen symbiosis are usually combined with green algal species and a smaller number of Cyanobacteria (Grube and Wedin, 2016). A possible explanation of the increase of lichen-associated fungi could be related to a direct increase of algae cells on the leaf surface due to the increased N availability.…”
Section: Discussionmentioning
confidence: 99%